Rancang Bangun Sistem Rekomendasi Lapak Usaha UMKM Kota Depok Berbasis Web Menggunakan Laravel dan React.js - Dwi Yulianti, Susana; Intan Anggari, Shierra; Kurniawan, Asep (Prosiding SEMNAS INOTEK (Seminar Nasional Inovasi Teknologi), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy but often face challenges in finding strategic business locations and building collaboration. This study aims to design a web-based business space recommendation system to support MSMEs in Depok City. The system was developed using the Waterfall model and a content-based filtering approach for its recommendation algorithm. Laravel and React.js were used for the system development, integrated with a Python Flask-based recommendation service. The results show that the system functions effectively with 100% success in black box testing. The System Usability Scale (SUS) score reached 79%, and the User Acceptance Test (UAT) score was 86.8%, indicating high user acceptance. The recommendation system achieved a precision rate of 80%, demonstrating the algorithm’s effectiveness in providing relevant location suggestions. This system is expected to serve as a digital solution to enhance MSMEs’ visibility and collaboration opportunities.